Effect of Lubricants on Properties of Conventional Tablets of Antihypertensive Drugs from Different Biopharmaceutical Classification System - Kavita, Dindawar; Supriya, B.M; Shivanand, Kolageri (Asian Journal of Pharmaceutical Research and Development, 2023)
Background: Hypertension is a long-term medical condition in which blood pressure in the arteries is elevated. Hypertension causes coronary artery disease, stroke, heartfailure; kidney diseases etc.to over come hypertension, antihypertensive drugs are used. Objectives: The aim of present work was to find out effectsof lubricants on properties of conventionaltablets containing antihypertensive drugs from different BCS class. Antihypertensive drugs suchas Metoprolol succinate, and Atenolol were selected which represented BCS class I, and II respectively. Methods: Lubricants are the essential components of all solid dosage forms. Sodium stearyl fumarate, a hydrophilic lubricant was compared with Magnesium stearate,a conventional hydrophobic lubricant. Uncoatedtabletswereprepared either by direct compression or wet granulation technique employing sodium stearyl fumarate or magnesium stearate as a lubricant at 1% or 2%, mixing time of lubricants was varied as 3 and 6mins. Results: Irrespective of class of drug, concentration, mixing time and processing method sodium stearyl fumarate turned out to be effective as tablet lubricant than Magnesium stearate. Both the Lubricants, when used at lower concentration and shorter mixing time resulted in superior tablets properties.Direc tcompression method gave better results than wet granulation technique. Both Sodium stearyl fumarate and Magnesium stearate (1%, 3min) were subjected to storage at400± 20C/ 75% RH for 90 days to check effect of aging and storage. Conclusion: According to at the end of storage period up on investigating for different tablet properties there were no significan tchanges observed.